2021
DOI: 10.1177/02698811211050556
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin microdosing does not affect emotion-related symptoms and processing: A preregistered field and lab-based study

Abstract: Background: Microdoses of psychedelics (i.e. a sub-hallucinogenic dose taken every third day) can reduce symptoms of depression, anxiety and stress according to anecdotal reports and observational studies. Research with medium to high doses of psilocybin points towards potential underlying mechanisms, including the modulation of emotion and interoceptive processing. Aims: In this preregistered study, we investigated whether psilocybin microdoses alter self-reported interoceptive awareness and whether repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 52 publications
0
39
0
Order By: Relevance
“…Nonetheless, authors acknowledged the potential confounding effects of breaking blind, as two-thirds of participants accurately guessed their condition 19 . Further analysis of the same participant pool did not identify differences in symptoms of anxiety and depression among microdosers relative to placebo 20 . However, the study noted that participants' prior experience with psychedelics in addition to low levels of depression and anxiety may have resulted in attenuated microdosing effects.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Nonetheless, authors acknowledged the potential confounding effects of breaking blind, as two-thirds of participants accurately guessed their condition 19 . Further analysis of the same participant pool did not identify differences in symptoms of anxiety and depression among microdosers relative to placebo 20 . However, the study noted that participants' prior experience with psychedelics in addition to low levels of depression and anxiety may have resulted in attenuated microdosing effects.…”
mentioning
confidence: 82%
“…The effective use of placebo has presented a challenge in the few published studies that have attempted such a design in the context of psychedelic microdosing 17,19,20 . Specifically, a prospective study of microdosing that used a self-blinding intervention to approximate placebo control among 191 participants over 4 weeks identified improvements in emotional well-being among microdosers, but noted that correct identification of condition was reported by 72% of participants complicating the ability to conclusively estimate the influence of placebo effects on observed changes.…”
mentioning
confidence: 99%
“…Related to this, Marschall et al (2022) report that psilocybin microdosing does not affect emotion-related symptoms and processing in a preregistered field and lab-based study. They conclude that further research in a substance-naïve population with clinical anxiety and depressive symptoms is needed to substantiate the potential beneficial effects of microdosing (Marschall et al, 2022). Finally, Rucker et al (2022) report the effects of psilocybin on cognitive and emotional functions in healthy participants.…”
mentioning
confidence: 84%
“…However, given recent findings on microdosing, double-blind, placebo-controlled experiments are required to substantiate these findings (Kuypers et al, 2019). Related to this, Marschall et al (2022) report that psilocybin microdosing does not affect emotion-related symptoms and processing in a preregistered field and lab-based study. They conclude that further research in a substance-naïve population with clinical anxiety and depressive symptoms is needed to substantiate the potential beneficial effects of microdosing (Marschall et al, 2022).…”
mentioning
confidence: 90%
“…Anecdotal evidence has suggested that using psilocybin delivered in low doses, colloquially “microdosing,” may bypass the mystical/hallucinatory experiences associated with higher doses of the drug while preserving long-term mental health improvements. However, when studied in a randomly controlled trial against a placebo, this effect has not been replicated [ 86 ]. As noted above, If the undesirable acute mystical/hallucinatory experience cannot be separated from the desirable long-lasting mental health benefits, then the medication will only be administrable under tightly controlled, supervised conditions.…”
Section: Reviewmentioning
confidence: 99%